Interphase microbial community characteristics in the fermentation cellar of Chinese Luzhou-flavor liquor determined by PLFA and DGGE profiles. (June 2015) - Ding, Xiaofei; Wu, Chongde; Huang, Jun; Zhou, Rongqing
Abstract: In view of the equilibrium of fermentation rate in the cellar mainly depends on interphase microflora, it is essential to exploit interphase microbial community characteristics to understand the metabolic regulation mechanism. The objective of this study was to investigate interphase microbial community structure in the fermentation cellar of Chinese Luzhou -flavor liquor via combining phospholipid fatty acids (PLFAs) and denaturing gradient gel electrophoresis (DGGE). The total microbial biomass analyzed by PLFA in the pit mud (PM: 25.52–103.38 nmol/g) and Zaopei (ZP: 29.96–64.50 nmol/g) was obviously higher than Huangshui (HS: 4.35–7.82 nmol/g), and was strongly correlated with pit age, which was validated by DGGE results. Among the specific microbial groups, 'gram-positive bacteria, anaerobe bacteria and fungi' dominated in the PM, while 'gram-positive bacteria, aerobe bacteria and fungi' predominated in the ZP and HS, respectively. Principal component analysis (PCA) based ordination of the relative PLFA abundance data segregated PM, ZP and HS. Eubacterial PCR-DGGE illustrated that a total of 31 bands belonged to five families ( Lactobacillaceae, Clostridiaceae, Porphyromonadaceae, Synergistaceae and Acetobacteraceae ) were identified, and 41.52% eubacteria were affiliated with Lactobacillaceae in the ZP, while 44.67% and 40.41% eubacteria were affiliated with Clostridiaceae in the PM and HS, respectively. Archaeal PCR-DGGE analysis demonstrated that Methanosaeta, Methanocorpusculum, Methanobrevibacter, Methanobacterium and Methanoculleus were the majority of archaea. Particularly, Methanosaeta, as acetrophic methanogens, increased gradually in the PM and HS with pit age, and decreased in the ZP, and no family Methanobacteriaceae was detected in the 30-year-PM. Furthermore, fungal community was dominated by genus Pichia . Highlights: Interphase microbial community characteristics in the cellar were analyzed for the first time. Differences of cellar of different pit ages were revealed by combined PLFA and PCR-DGGE. The total biomass in the pit mud and Zaopei was obviously higher than Huangshui . Methanosaeta increased in the pit mud and Huangshui with pit age, and decreased in the Zaopei . Community characteristics in the pit mud and Zaopei simply determined the unique feature of Huangshui .